RANCANG BANGUN SISTEM INFORMASI PERIZINAN TATA LINGKUNGAN DINAS LINGKUNGAN HIDUP BERBASIS WEB - Putra, Yusuf Wahyu Setiya; Mila, Tri Yusuf Suyatno; Mila, Didin Herlinudinkhaji; adminjfik, adminjfik (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2022)
This web-based designing and building of the Environmental Planning Licensing Informastion System of Kendal Regency was created to help and improve the licensing services in the Environmental Management Field of the Environmental Service of Kendal Regency. The purpose of this study was to create a web-based data processing information system aimed at administrator and officers of the Environmental Service of Kendal Regency and also visitors or permit applicants to observe their submitted application.This research used data collection methods by observation, interviews, and literature studies as well as system development methods using the Linear Sequential Model or Watefall Model. The Waterfall Method has some steps, namely data collection, analysis, design, implementation / coding, testing, operation, and maintenance. The reason for choosing this method was the method must be carried out systematically or sequentially and each step has its own focus, so that the system can be developed based on the wish. The system design method used is the Data Flow Diagram (DFD) method.The result of this study is an environmental planning licensing informastion system that manages submission data, licensing data, submission requirements, checklist requirements, photo data, message boxes, and visitor pages with a search system to help the applicants finding information relate to the processing of the file that has been submitted.